Cyclohexanecarboxyl-Coenzyme A (CoA) and Cyclohex-1-ene-1-Carboxyl-CoA Dehydrogenases, Two Enzymes Involved in the Fermentation of Benzoate and Crotonate in Syntrophus aciditrophicus - Kung, Johannes W. (American Society for Microbiology, 2013)
The strictly anaerobic Syntrophus aciditrophicus is a fermenting deltaproteobacterium that is able to degrade benzoate or crotonate in the presence and in the absence of a hydrogen-consuming partner. During growth in pure culture, both substrates are dismutated to acetate and cyclohexane carboxylate. In this work, the unknown enzymes involved in the late steps of cyclohexane carboxylate formation were studied. Using enzyme assays monitoring the oxidative direction, a cyclohex-1-ene-1-carboxyl-CoA (Ch1CoA)-forming cyclohexanecarboxyl-CoA (ChCoA) dehydrogenase was purified and characterized from S. aciditrophicus and after heterologous expression of its gene in Escherichia coli. In addition, a cyclohexa-1,5-diene-1-carboxyl-CoA (Ch1,5CoA)-forming Ch1CoA dehydrogenase was characterized after purification of the heterologously expressed gene. Both enzymes had a native molecular mass of 150 kDa and were composed of a single, 40- to 45-kDa subunit; both contained flavin adenine dinucleotide (FAD) as a cofactor. While the ChCoA dehydrogenase was competitively inhibited by Ch1CoA in the oxidative direction, Ch1CoA dehydrogenase further converted the product Ch1,5CoA to benzoyl-CoA. The results obtained suggest that Ch1,5CoA is a common intermediate in benzoate and crotonate fermentation that serves as an electron-accepting substrate for the two consecutively operating acyl-CoA dehydrogenases characterized in this work. In the case of benzoate fermentation, Ch1,5CoA is formed by a class II benzoyl-CoA reductase; in the case of crotonate fermentation, Ch1,5CoA is formed by reversing the reactions of the benzoyl-CoA degradation pathway that are also employed during the oxidative (degradative) branch of benzoate fermentation.